2022
DOI: 10.3390/mi13101587
|View full text |Cite
|
Sign up to set email alerts
|

Novel Endovascular Interventional Surgical Robotic System Based on Biomimetic Manipulation

Abstract: Endovascular therapy has emerged as a crucial therapeutic method for treating vascular diseases. Endovascular surgical robots have been used to enhance endovascular therapy. However, to date, there are no universal endovascular surgical robots that support molds of different types of devices for treating vascular diseases. We developed a novel endovascular surgical robotic system that can independently navigate the intravascular region, advance and retract devices, and deploy stents. This robot has four featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Despite significant advances in endovascular technologies, the actual procedural methodology for EVAR has remained unaltered since the past 20 years. This novel endovascular robotic system might reduce the occupational risks associated with manual EVAR, in addition to contributing to a higher degree of precision and control during EVAR [ 29 ]. This study lays the foundation for the future development of efficient robotic platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant advances in endovascular technologies, the actual procedural methodology for EVAR has remained unaltered since the past 20 years. This novel endovascular robotic system might reduce the occupational risks associated with manual EVAR, in addition to contributing to a higher degree of precision and control during EVAR [ 29 ]. This study lays the foundation for the future development of efficient robotic platforms.…”
Section: Discussionmentioning
confidence: 99%
“…The intersection of novel materials and robotics has catalyzed groundbreaking advancements in the cardiovascular field, promising innovative solutions for diagnosis, intervention, and postoperative care ( 46 , 47 ). The development and integration of novel materials, such as biocompatible polymers and shape memory alloys, offer unprecedented opportunities for designing cardiovascular devices with enhanced durability and tailored biomechanical properties.…”
Section: Novel Materialsmentioning
confidence: 99%
“…Clamping maintains the endovascular device in a locked state, making it completely follow the movement of the manipulator to advance, retract, and rotate. Continuous rotation is helpful in speci c actions such as arterial navigation [34] and stent-graft deployment.…”
Section: Design Of the Endovascular Surgical Robotmentioning
confidence: 99%
“…On the basis of previous research [34], we rst reported automated TEVAR and EVAR performed by our novel endovascular surgical robot and elaborated on the automatic processes. We demonstrated the performance of the novel endovascular surgical robot of Level 3B.…”
Section: Introductionmentioning
confidence: 99%